Condensational growth of water droplets in an external electric field at different temperatures. Issue 12 (1st December 2020) - Gabyshev, Dmitrii N.; Fedorets, Alexander A.; Klemm, Otto
Abstract: The condensational growth of water droplets in technical and natural systems varies with environmental conditions such as droplet size, droplet composition, air humidity, temperature, and turbulence. This contribution addresses the influence of external electrical fields on the condensation process. Although electrical fields exist in the atmosphere, for example in thunderstorm clouds, and although it is generally accepted that electrical fields exert an influence on the condensation process, no quantitative description of this influence at ambient temperatures exists. We present laboratory experiments and a theoretical model to further develop understanding of the influence of electric fields on condensation at various temperatures. The levitated droplet cluster technology is applied to study the kinetics of droplet growth in an external electric field at temperatures between 50 °C and 70 °C. The theoretical model is designed to mirror the experimental conditions as precisely as possible. Experimental and kinetic model results are in qualitative agreement in that the relative contribution of the electrically induced contribution to total condensation reduces with increasing temperature. Vice versa, the electrically induced condensation significance is expected to further increase with decreasing temperatures below 50 °C. We expect that electro-condensation will be the dominating process at room temperatures and even more at temperatures near 0 °C, at electric field strengths typical for clouds. Further studies are needed to extend the experimental and theoretical temperature range to conditions typical for clouds in the atmosphere. Copyright © 2020 American Association for Aerosol Research